Longitudinal vehicle control with active braking using model-free controllers. - França, Rodrigo de Marca (2022)
With the advancement of automotive technology, the use of Advanced Driver- Assistance Systems (ADAS) has become increasingly common. These systems allow an increase in comfort, safety, reliability, and overall efficiency of vehicles, helping the driver in various driving-related tasks. One of these systems is the Adaptive Cruise Control (ACC) which is capable of longitudinally controlling vehicles, allowing them to maintain fixed speeds or decelerate vehicles in emergency situations. In this work, modelfree intelligent PID (iPID) control techniques are used for longitudinal control of vehicles without the need to complex mathematical models. In particular, this work uses an intelligent Proportional (iP) control to longitudinally control a simulated vehicle, replacing the driver and controlling the acceleration and braking simultaneously. The most interesting features of this controller are discussed, especially its ability to resist noise. Additional tests with an equivalent classical Proportional Integral (PI) controller are performed for comparison purposes. The work also proposes a real-time least square-based estimator for the used Model-Free Control (MFC) parameter, creating an Adaptive Model-Free Control (AMFC) family named intelligent PID with estimator (iPID). Both an iP and iP controllers are used to longitudinally control vehicles simulated in a commercial vehicle simulator capable of highly complex vehicle dynamics simulations. Several tests from the European New Car Assessment Programme (Euro NCAP) were performed to test the controllers response to emergencies, with very good results.